Manipulating assimilate availability provides insight into the genes controlling grain size in sorghum. (13th August 2021) - Tao, Yongfu; Trusov, Yuri; Zhao, Xianrong; Wang, Xuemin; Cruickshank, Alan W.; Hunt, Colleen; van Oosterom, Erik J.; Hathorn, Adrian; Liu, Guoquan; Godwin, Ian D.; Botella, Jose R.; Mace, Emma S.; et al.
SUMMARY: Variation in grain size, a major determinant of grain yield and quality in cereal crops, is determined by both the plant's genetic potential and the available assimilate to fill the grain in the absence of stress. This study investigated grain size variation in response to variation in assimilate supply in sorghum using a diversity panel ( n = 837) and a backcross‐nested association mapping population ( n = 1421) across four experiments. To explore the effects of genetic potential and assimilate availability on grain size, the top half of selected panicles was removed at anthesis. Results showed substantial variation in five grain size parameters with high heritability. Artificial reduction in grain number resulted in a general increase in grain weight, with the extent of the increase varying across genotypes. Genome‐wide association studies identified 44 grain size quantitative trait locus (QTL) that were likely to act on assimilate availability and 50 QTL that were likely to act on genetic potential. This finding was further supported by functional enrichment analysis and co‐location analysis with known grain number QTL and candidate genes. RNA interference and overexpression experiments were conducted to validate the function of one of the identified gene, SbDEP1, showing that SbDEP1 positively regulates grain number and negatively regulates grain size by controlling primary branching in sorghum. Haplotype analysis of SbDEP1 suggested a possible role in racial differentiation. The enhanced understanding of grain size variation in relation to assimilate availability presented in this study will benefit sorghum improvement and have implications for other cereal crops. Significance Statement: This study identified 44 grain size quantitative trait locus that were likely to act on assimilate availability and 50 quantitative trait loci that were likely to act on genetic potential through a treatment of removing the half panicle at anthesis across four field experiments of two large populations. The effect of assimilate availability on grain size was further demonstrated through functional investigation of a candidate gene, SbDEP1 .